2006
DOI: 10.1038/ja.2006.74
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses Lead to Novel Secondary Metabolites

Abstract: Genomic analyses of Amycolatopsis orientalis ATCC 43491 strain, deposited as a vancomycin producer, revealed the presence of genetic loci for the production of at least 10 secondary metabolites other than vancomycin. One of these gene clusters, which contained a type I polyketide synthase, was predicted to direct the synthesis of novel class of compound, a glycosidic polyketide ECO-0501 (1). Screening of culture extracts for a compound with the predicted physicochemical properties of the product from this locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 11 publications
2
75
0
3
Order By: Relevance
“…29 other secondary metabolite gene clusters were found to be present in the genome among which one of the clusters encoded for the synthesis of polyketide synthase compound ECO-0501. As this cluster and corresponding product was already identified and reported in literature [45], the focus shifted to identification of some other biosynthetic gene cluster. A type III PKS/NRPS hybrid gene cluster that showed high similarity to other glycopeptide gene clusters like balhimycin and teicoplanin was identified.…”
Section: Amycolatopsis Japonica Mg417-cf17mentioning
confidence: 99%
“…29 other secondary metabolite gene clusters were found to be present in the genome among which one of the clusters encoded for the synthesis of polyketide synthase compound ECO-0501. As this cluster and corresponding product was already identified and reported in literature [45], the focus shifted to identification of some other biosynthetic gene cluster. A type III PKS/NRPS hybrid gene cluster that showed high similarity to other glycopeptide gene clusters like balhimycin and teicoplanin was identified.…”
Section: Amycolatopsis Japonica Mg417-cf17mentioning
confidence: 99%
“…The two singlet peaks for methyl groups at d 1.45 and d 1.44 suggested that compound 1 is an equilibrium mixture of 2R and 2S anomers. This was confirmed by measuring the 1 H NMR in benzene-d 6 , where these two methyl signals occurred at a very different ratio. The 1 H NMR spectrum of 2 was similar to that of 1.…”
Section: Resultsmentioning
confidence: 62%
“…Analyses of these gene clusters led us to conclude that these microorganisms produce members of a group of very closely related secondary metabolites. Here, we report the isolation and identification of three new 5-alkenyl-3,3(2H)-furanones from these two streptomycetes [6]. …”
mentioning
confidence: 99%
“…Recent molecular approaches have successfully revealed the presence of large numbers of cryptic PKS gene in the genome of Streptomyces spp. Since the presence of novel PKS genes in organisms provides good clues for production of novel polyketides, the sequencing of PKS genes is often used as a screening method for the discovery of novel polyketides (Ayuso et al, 2005;McAlpine et al, 2005;Banskota et al, 2006). The objective of this work was to assess the use of a PCR-based technique in the preliminary screening for microorganisms which were as producer of potential novel polyketide against plant pathogen fungi.…”
Section: Introductionmentioning
confidence: 99%